Quality Assessment of the Permian Coals from Dighipara Basin, Bangladesh Based On Proximate, Ultimate and Microscopic Analyses (Journal of Bangladesh Academy of Sciences, 2015)
Assessment of coal quality based on proximate (volatile matter, fixed carbon, ash, moisture), ultimate (C, H, N, S, O) and microscopic (macerals, microlithotypes, coal facies) analyses of the Permian coals from the Dighipara basin, Bangladesh was carried out. A total of 11 coal core samples collected from two bore holes of Dighipara basin were analyzed. ASTM standards were followed for proximate and ultimate analyses. ICCP systems were used for the microscopic study. Thermal maturity, physical characteristics of the coal seams, gross calorific value and atomic ratios of H/C and O/C were also considered.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 177-194, 2015